Understanding the Role of Order in Y‐Series Non‐Fullerene Solar Cells to Realize High Open‐Circuit Voltages - Stefan Zeiske (Advanced Energy Materials, 2022)
Non-fullerene acceptors (NFAs) as used in state-of-the-art organic solar cells feature highly crystalline layers that go along with low energetic disorder. Here, the crucial role of energetic disorder in blends of the donor polymer PM6 with two Y-series NFAs, Y6, and N4 is studied. By performing temperature-dependent charge transport and recombination studies, a consistent picture of the shape of the density of state distributions for free charges in the two blends is developed, allowing an analytical description of the dependence of the open-circuit voltage VOC on temperature and illumination intensity. Disorder is found to influence the value of the VOC at room temperature, but also its progression with temperature. Here, the PM6:Y6 blend benefits substantially from its narrower state distributions. The analysis also shows that the energy of the equilibrated free charge population is well below the energy of the NFA singlet excitons for both blends and possibly below the energy of the populated charge transfer manifold, indicating a down-hill driving force for free charge formation. It is concluded that energetic disorder of charge-separated states has to be considered in the analysis of the photovoltaic properties, even for the more ordered PM6:Y6 blend.